2021
DOI: 10.1002/anie.202016822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sequence and Base Composition on the CD and TDS Profiles of i‐DNA

Abstract: The i-motif DNA, also knowna si -DNA, is an oncanonical DNAs econdary structure formed by cytosine-rich sequences,c onsisting of two intercalated parallel-stranded duplexes held together by hemi-protonated cytosine-cytosine + (C:C + )base pairs.The growing interest in the i-DNAstructure as atarget in anticancer therapyincreases the need for tools for arapid and meaningful interpretation of the spectroscopic data of i-DNAsamples.Herein, we analyzed the circular dichroism (CD) and thermal difference UV-absorbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 31 publications
(41 reference statements)
3
32
0
Order By: Relevance
“…To illustrate the procedure, the temperature dependent UV spectra at pH 6.0 of 44L1 are shown in Figures 3A-B. The temperaturedependent thermal difference spectra (TDS) 24 were obtained by subtracting the UV spectrum of fully unfolded species at the highest temperature (90 °C) from the spectra of fully or partially folded species at a lower temperature, between 5 and 90 °C (Figures 3C-D). The TDS positive peak around 240 nm and negative peak around 295 nm indicate the formation of i-DNA 53 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate the procedure, the temperature dependent UV spectra at pH 6.0 of 44L1 are shown in Figures 3A-B. The temperaturedependent thermal difference spectra (TDS) 24 were obtained by subtracting the UV spectrum of fully unfolded species at the highest temperature (90 °C) from the spectra of fully or partially folded species at a lower temperature, between 5 and 90 °C (Figures 3C-D). The TDS positive peak around 240 nm and negative peak around 295 nm indicate the formation of i-DNA 53 .…”
Section: Resultsmentioning
confidence: 99%
“…As cytosine protonation at the N3 position is essential for formation of the hemi-protonated base pairs, stability and unfolding/folding rates of i-DNA depend on pH [9][10][11][12][13][14][15][16][17][18][19][20] . i-DNA stability is often modest under physiological conditions 11,13,21 , but some i-DNA structures have been shown to remain folded at neutral pH 11,[13][14][15][16][20][21][22][23][24][25][26] . In-cell NMR 20,27 and experiments with an i-DNA-specific antibody 28 recently demonstrated that i-DNAs are present in human cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the Tel 23 G4 sequence showed a CD spectrum having two positive bands at 290 and 270 nm and a weak negative band at 240 nm, consistent with the formation of a hybrid [3+1] G4 folding topology. As for Bcl-2 iM, c-Myc iM , and hTeloC iM , all of them exhibited a CD spectrum with a positive band at 288 nm and a negative one at around 260 nm, which are characteristic values of iM formation [ 48 ], while the Hairpin showed a positive band at around 280 nm and a negative one at ~250 nm in the CD spectrum, confirming duplex formation ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 95%
“…At pH 5.2, the CD spectra of both BCL2 and KRAS sequences exhibited the characteristic iM profile, i.e., a strong positive band at 288 nm and a negative one at 264 nm. 62 On increasing the pH to 6.6, a shift of the maximum to 285 nm was observed for both oligonucleotides, suggesting the formation of a certain amount of hairpin conformation. Upon further increase of the pH to 7.8, the CD spectra of both DNA sequences exhibited a significant intensity drop of the positive band along with the shift of the maximum to 280 nm.…”
Section: Circular Dichroism (Cd) Experiments In Dilute Solution and M...mentioning
confidence: 93%